Sputum IL-25, IL-33 and TSLP, IL-23 and IL-36 in airway obstructive diseases. Reduced levels of IL-36 in eosinophilic phenotype. (April 2021) - Moermans, C.; Damas, K.; Guiot, J.; Njock, M.S.; Corhay, J.L.; Henket, M.; Schleich, F.; Louis, R.
Highlights: First report on IL-36 sputum levels in chronic airway obstructive diseases. IL-36 level was decreased in patients with an eosinophilic airway inflammation. There is an implication of IL-36 and IL-23 in airway neutrophilic inflammation. A negative correlation was noted between TSLP expression and sputum eosinophils. Overall, alarmins/cytokines (IL-23 and IL-36) levels did not differ from controls. Abstract: Introduction: Alarmins ((IL-25, IL-33 and thymic stromal lymphopoietin (TSLP)) are known to promote Th2 inflammation and could be associated with eosinophilic airway infiltration. They may also play a role in airway remodeling in chronic airway obstructive diseases such as asthma and chronic obstructive pulmonary disease (COPD). IL-23 and IL-36 were shown to mediate the neutrophilic airway inflammation as seen in chronic airway obstructive diseases. Objectives: The purpose of this project was to determine the expression and the production of these cytokines from induced sputum (IS) in patients with chronic airway obstructive diseases including asthmatics and COPD. The relationship of the mediators with sputum inflammatory cellular profile and the severity of airway obstruction was assessed. Methods: The alarmins (IL-25, IL-33 and TSLP) as well as IL-23 and IL-36 concentrations were measured in IS from 24 asthmatics and 20 COPD patients compared to 25 healthy volunteers. The cytokines were assessed by ELISA in the IS supernatant and by RT-qPCR in the IS cells. Results: At protein level, no difference was observed between controls and patients suffering from airway obstructive diseases regarding the different mediators. IL-36 protein level was negatively correlated with sputum eosinophil and appeared significantly decreased in patients with an eosinophilic airway inflammation compared to those with a neutrophilic profile and controls. At gene level, only IL-36, IL-23 and TSLP were measurable but none differed between controls and patients with airway obstructive diseases. IL-36 and IL-23 were significantly increased in patients with an neutrophilic inflammatory profile compared to those with an eosinophilic inflammation and were correlated with sputum neutrophil proportions. None of the mediators were linked to airway obstruction. Conclusions: The main finding of our study is that patients with eosinophilic airway inflammation exhibited a reduced IL-36 level which could make them more susceptible to airway infections as IL-36 is implicated in antimicrobial defense. This study showed also an implication of IL-36 and IL-23 in airway neutrophilic inflammation in chronic airway obstructive diseases.